2002
DOI: 10.1074/jbc.m101632200
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Ethanol Exposure Potentiates Lipopolysaccharide Liver Injury Despite Inhibiting Jun N-terminal Kinase and Caspase 3 Activation

Abstract: Although ethanol is known to sensitize hepatocytes to tumor necrosis factor (TNF) lethality, the mechanisms involved remain controversial. Recently, others have shown that adding TNF␣ to cultures of ethanol-pretreated hepatocytes provokes the mitochondrial permeability transition, cytochrome c release, procaspase 3 activation, and apoptosis. Although this demonstrates that ethanol can sensitize hepatocytes to TNF-mediated apoptosis, the hepatic inflammation and ballooning hepatocyte degeneration that typify al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 82 publications
4
62
0
Order By: Relevance
“…Second, even when early stages of apoptotic signaling are not impaired, low cellular energy levels may prevent the completion of the apoptotic signaling cascade, resulting in secondary necrosis (sometimes coined "necroptosis"; Malhi et al, 2006). A similar imbalance between increases in apoptosis and necrosis was observed by Koteish et al (2002) in a model of enhanced LPS-induced liver damage caused by chronic ethanol exposure. In particular, the authors of that study found that ethanol enhances LPS-induced necrosis but blunts apoptosis (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…Second, even when early stages of apoptotic signaling are not impaired, low cellular energy levels may prevent the completion of the apoptotic signaling cascade, resulting in secondary necrosis (sometimes coined "necroptosis"; Malhi et al, 2006). A similar imbalance between increases in apoptosis and necrosis was observed by Koteish et al (2002) in a model of enhanced LPS-induced liver damage caused by chronic ethanol exposure. In particular, the authors of that study found that ethanol enhances LPS-induced necrosis but blunts apoptosis (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…LPS directly causes liver injury by mechanisms involving inflammatory cells such as Kupffer cells, and chemical mediators such as superoxide, nitric oxide, and tumor necrosis factor (TNFa) and other cytokines [31,81,91]. In addition, LPS potentiates liver damage induced by hepatotoxins including ethanol [10,19,30,46,59,84]. In experimental alcoholic liver disease, the combination of LPS and chronic ethanol produces hepatic necrosis and inflammation [30,46,59,84].…”
Section: Kupffer Cells and Alcoholic Liver Diseasementioning
confidence: 99%
“…In addition, LPS potentiates liver damage induced by hepatotoxins including ethanol [10,19,30,46,59,84]. In experimental alcoholic liver disease, the combination of LPS and chronic ethanol produces hepatic necrosis and inflammation [30,46,59,84]. Ethanol alters gut microflora, the source of LPS, and ethanol increases the permeability of the gut, thus increasing the distribution of LPS from the gut into the portal circulation (endotoxemia).…”
Section: Kupffer Cells and Alcoholic Liver Diseasementioning
confidence: 99%
“…Thus changes in the expression of genes have been implicated in the development of alcoholic liver diseases (ALD). Genes that are involved in ethanol metabolism (Morimoto et al, 1993;Ronis et al, 1993;Deaciuc et al, 2004a,b) cell signaling (Mochly-Rosen et al, 1988;Gordon et al, 1986;Hong et al, 2002a,b) and apoptosis (Yacoub et al, 1995;Deaciuc et al, 1999;Deaciuc et al, 2002a,b;Koteish et al, 2002) are highly sensitive to alcohol. Micro-array studies have also shown profile of hepatic gene expressions induced by alcohol consumption (Tadic et al, 2002;Deaciuc et al, 2004a,b;French et al, 2005).…”
Section: Introductionmentioning
confidence: 99%